La représentation du corps dans la pensée et la médecine chinoise - Boudon, Pierre (Anthropologica, 2022)
In this paper, we have tried to define the concept of the body implicit in the medical practice of China acupuncture. This conception is holistic in that it is linked to the cultural patterns which form Chinese thought with its theory of Yin-Yang and the Five Elements. Consequently, two kinds of medicine - occidental and Chinese - appear to be incomparable in the sense that each of these systems of thinking organizes and / or shapes the physiology of the body according to distinct principles.